2022
DOI: 10.1186/s12991-022-00423-0
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between negative life events and non-suicidal self-injury (NSSI) among Chinese junior high school students: the mediating role of emotions

Abstract: Background Adolescent non-suicidal self-injury (NSSI) is common and adolescence is the most common period of first self-injury, and the occurrence of NSSI is influenced by negative life events and emotional symptoms. The mediating role of emotional symptoms in the interaction between negative life events and NSSI has not been carefully investigated yet. Methods For middle school students in three schools in a Chinese province, the Adolescents Self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Instead, they may engage in a process of contemplation and recollection, often facilitated by rumination. In cases where negative emotions persist and intensify to a certain degree, there is an increased likelihood of the individual developing non-suicidal self-injury behaviors ( 25 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, they may engage in a process of contemplation and recollection, often facilitated by rumination. In cases where negative emotions persist and intensify to a certain degree, there is an increased likelihood of the individual developing non-suicidal self-injury behaviors ( 25 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a meta-analysis included 46 studies additionally demonstrated that rumination exerted a significant influence on NSSI ( 24 ). Although numerous studies have pointed out that emotions mediate the relationship between major life events and NSSI ( 25 ). There is a limited body of research that examines the role of rumination, which encompasses negative emotions and cognitive functioning, in the relationship between major life events and NSSI.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with a history of childhood trauma often exhibit a lower capacity for environmental adaptation, demonstrating a relatively lower resilience to negative life events, such individuals experience a higher incidence of negative life events during adulthood, 40 , 41 which are viewed as potential risk factors for adolescent NSSI behaviors. 42 Adolescents are at a turning point in their life development. Since the emergence of COVID-19, social isolation caused by concomitant home isolation, infected family and friends, family economic pressure caused by property loss, uncertainty about the future, and anxiety and fear of infection have had serious negative effects on the physical and mental health of adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescence is crucial for psychological growth and is affected by negative events in families, schools, and physical and psychological aspects ( 5 ). These events can directly impact depressive emotions and indirectly influence the emotions by affecting ruminant thinking ( 6 ), particularly in individuals with disruptions to default mode network functional connectivity ( 7 ).…”
Section: Introductionmentioning
confidence: 99%